Isolation and Identification of Trehalase from Pullularia pullulans - Merdinger, Emanuel (1971)
Trehalase has been isolated from Pullularia pullulans. The enzyme, which is specific for trehalose, was purified approximately 800-fold. The optimal pH was found to be 4.0 and the Michaelis dissociation constant, K(m), was determined to be 3.2 × 10(−3)m.